The influence of digital marketing tools on generating business from a personal stylist (Revista Brasileira de Contabilidade e Gestão, 2019)
Digital marketing is increasingly present in people's daily lives, even if not very much perceived. It simplifies the lives of everyone involved in the process. Likewise, the theme "fashion" has gained relevance because people understand that they need to take care of appearance, both in personal and professional environment. Thus, this article seeked to identify which digital marketing strategies influenced the business generation of a personal stylist. The research was carried out using a qualitative method, of the exploratory type with a convenience sampling. The data analysis was performed through the interpretation of a semi-structured interview conducted with a personal stylist who is working for five years in this segment. Through the realized research, it was realized that digital marketing is a strong influencer in the generation of business and to narrow relationship with the customers.
Keywords: Marketing; Fashion; Personal Stylist